Public Relations in the Digital Age: Immersive Models - Shilina, М.Г; Ishanova, А.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
The article presents current foundations for the scientific and theoretical systematization of parameters of digital immersive Public Relations. In an era of extreme saturation with digital technologies (primarily artificial intelligence) the basic research optics of PR is communicative, focused on human-centered communication. For the first time, the article introduces an approach to solving the scientific problem of conceptualizing relevant human-centered immersive characteristics of digital technologies in PR, with the aim of defining their relevant model. Based on a desk study of digital communication models in PR (Internet, VR), the features of their immersiveness are presented. The specifics of the format for involving the target audience in a virtual environment for the experimental acquisition of real experience necessitate the identification of a special subtype in the classification of technology-mediated public relations communication: immersive PR. The study identifies two levels of digital immersiveness in PR: the immersiveness of the Internet as primary, and the immersiveness of virtual reality technologies as mediated. It defines the multi-level and polysemantic nature of content and its consumption, and highlights the characteristics of the target audience as an actor-prosumer of immersive digital experience. For the first time, working definitions of basic concepts in this field are introduced, in particular: immersiveness in PR, augmented and virtual reality as a PR tool, and models of digital immersive communication in PR. Immersive PR projects demonstrate trends in PR shifting from rational to emotional formats, as immersive technologies are visual. Immersive PR projects, for the first time, provide a high level of simulation technologies for communication aimed at the experimental creation of new user experiences, which brings about new technological and ethical risks, and determines the need for new parameters for building trust in PR, etc., as well as vectors for further research. An expert survey confirms the authors’ proposed theses.